A method of holographic magnification based on Fresnel diffraction. Issue 6 (10th June 2016) - Gan, Feng‐Jiao; Wang, Di; Wang, Cui; Wang, Jun; Wang, Qiong‐Hua
Abstract: In this paper, we propose a method of holographic magnification based on Fresnel diffraction. Similarity principle of Fourier transform is used in convolution algorithm in order to adjust the size of the reconstructed image. With the splicing technology based on a spatial light modulator, the reconstructed images can be magnified. By combining the similarity principle of Fourier transform with the splicing technology, the reconstructed images can be further magnified to eight times, which is verified by the experiments. Abstract : We propose a method of holographic magnification based on Fresnel diffraction. The similarity principle of Fourier transform is used in a convolution algorithm in order to adjust the size of the reconstructed image. By combining the similarity principle of Fourier transform with splicing technology, the reconstructed images can be further magnified eight times.